2018
DOI: 10.1021/acs.iecr.8b02139
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Controllable Preparation of Ultramicroporous Biomass-Derived Carbons and Application on Selective Adsorption of Gas-mixtures

Abstract: It is very challenging to prepare biomass-derived porous carbons with well-confined ultramicropores. Traditionally, biomass-derived carbons, via a chemical activation process, possess wide pore size distributions from micropores to macropores. Outstanding BET surface area of 2676 ± 107 m2 g–1 was obtained with excellent CO2 uptake of 6.15 and 2.26 mmol g–1 under 1 and 0.15 bar at 273 K. Furthermore, the outstanding CO2/N2, CO2/CH4, and CH4/N2 selectivities of 43.5, 7.4, and 5.9 were obtained on an OTS-1-550 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…A comparison between the mass ratio of KOH‐to‐carbon precursor used to prepare SCs in this work, as well as other previously reported carbon materials that exhibit excellent adsorption performance (SFRH polymer‐based carbons 33 ; sawdust‐derived mechanochemically carbons 34 ; OTS‐derived carbons 35 ; and sawdust‐based carbons 36 ), is presented in Figure 5. This comparison reveals that the mass ratios of KOH‐to‐carbon precursor are in the range of 0.06–0.23 for SCs prepared in this work, ~93% less than those prepared from traditional chemical activation methods.…”
Section: Resultsmentioning
confidence: 73%
“…A comparison between the mass ratio of KOH‐to‐carbon precursor used to prepare SCs in this work, as well as other previously reported carbon materials that exhibit excellent adsorption performance (SFRH polymer‐based carbons 33 ; sawdust‐derived mechanochemically carbons 34 ; OTS‐derived carbons 35 ; and sawdust‐based carbons 36 ), is presented in Figure 5. This comparison reveals that the mass ratios of KOH‐to‐carbon precursor are in the range of 0.06–0.23 for SCs prepared in this work, ~93% less than those prepared from traditional chemical activation methods.…”
Section: Resultsmentioning
confidence: 73%
“… 35 The D band represents the subsistent disorder carbon structures, and the G band corresponds to the vibration of sp 2 ‐hybridized C atoms in the graphitic layer. The peak intensity ratio of D and G bands ( I D / I G ) is regarded as an index of the graphitization degree 18 : the high I D / I G value for GOC‐4 indicated that a higher number of defects were generated with increased KOH/GOCs ratios. The additional 2D bands at 2780 cm −1 indicated the existence of graphene‐like layers 36 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Ma and coworkers prepared a novel MOF—ATC‐Cu (H 2 ATC = 1,3,5,7‐adamantane tetracarboxylic acid)—as a new type of CH 4 nano‐trap that exhibited a benchmark CH 4 capacity of 2.9 mmol/g and CH 4 /N 2 selectivity (50/50, v/v) of 9.7 at 298 K and 1 bar 17 . Nevertheless, the long‐term stability and manufacturing cost need to be optimized to realize commercial applications 18,19 . Recently, our group has reported the successful down‐sized zeolite (ZK‐5) prepared via β ‐cyclodextrin mediating: the nano‐sized ZK‐5 (50–100 nm) showed an enhanced CH 4 separation capacity of 1.34 mmol/g and CH 4 /N 2 selectivity (20/80, v/v) of 4.2 at 298 K and 1 bar 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the mechanism of CH 4 ‐selective adsorbents for CH 4 /N 2 separation is predominantly equilibrium‐based. Porous carbons and MOFs are extensively studied porous materials for CH 4 /N 2 separation [13b,e, 14c,d, 37] . Some zeolites have been tried and tested for CH 4 /N 2 separation as well [38]…”
Section: Methane–nitrogen Separationmentioning
confidence: 99%
“…In earlier studies, porous carbons were treated by loading other chemicals, such as Br 2 , ICl, or MoO 2 , onto the adsorbents to improve their CH 4 /N 2 separation performance [11a, 12a] . In recent years, heteroatom‐doped porous carbons and activated carbons derived from biomass have been explored [13b,e, 14c, 39] . N‐rich microporous carbons derived from N‐containing polymers were obtained by a solvent‐free method; they possessed narrow pore size distributions (ca.…”
Section: Methane–nitrogen Separationmentioning
confidence: 99%